Assessing cardiovascular risk by using the fat attenuation index in coronary CT angiography - Klüner, LV; Oikonomou, EK; Antoniades, C (Radiological Society of North America, 2021)
Perivascular adipose tissue mapping by means of the coronary CT angiography (CCTA)–derived fat attenuation index is a recently developed method to noninvasively detect coronary inflammation and atherosclerotic changes at CCTA, with incremental prognostic value over and above traditional risk factors.